Mechanisms leading from systemic autoimmunity to joint-specific disease in rheumatoid arthritis - Catrina, Anca I.; Svensson, Camilla I.; Malmstrom, Vivianne; Schett, Georg; Klareskog, Lars (Nature Reviews Rheumatology, 2016)
A key unanswered question in the pathophysiology of rheumatoid arthritis (RA) is how systemic autoimmunity progresses to joint-specific inflammation. In patients with seropositive RA (that is, characterized by the presence of autoantibodies) evidence is accumulating that immunity against post-translationally modified (such as citrullinated) autoantigens might be triggered in mucosal organs, such as the lung, long before the first signs of inflammation are seen in the joints. However, the mechanism by which systemic autoimmunity specifically homes to the joint and bone compartment, thereby triggering inflammation, remains elusive. This Review summarizes potential pathways involved in this joint-homing mechanism, focusing particularly on osteoclasts as the primary targets of anti-citrullinated protein antibodies (ACPAs) in the bone and joint compartment. Osteoclasts are dependent on citrullinating enzymes for their normal differentiation and are unique in displaying citrullinated antigens on their cell surface in a non-inflamed state. The binding of ACPAs to osteoclasts releases the chemokine IL-8, leading to bone erosion and pain. This process initiates a chain of events that could lead to attraction and activation of neutrophils, resulting in a complex series of proinflammatory processes in the synovium, eventually leading to RA.
EVALuna2:13384